2022
DOI: 10.1021/acscatal.2c03994
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Determined Single, Double, and Triple C–H Arylation of Aryl Phosphines at Will

Abstract: Controllable ortho-C–H arylation of aryl phosphines would provide a foundation for the modular synthesis of electronically and sterically tunable biaryl phosphines. However, this central task is challenging owing to the unfavorable four-membered cyclometalation and high tendency to undergo further interannular arylation. Herein phenolic compounds have been found to be effective ligands to determine single, double, or triple C–H arylation at will, providing a streamlined and practical synthetic approach to acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 45 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…After we filed our work report, the You research group reported similar work on the phosphine-directed rhodium-catalyzed arylation reaction. 35 Differing from our strategy, they achieved control over the number of C−H arylations by adding various types of phenol ligands.…”
Section: C−h Arylation Of Phosphinesmentioning
confidence: 99%
See 1 more Smart Citation
“…After we filed our work report, the You research group reported similar work on the phosphine-directed rhodium-catalyzed arylation reaction. 35 Differing from our strategy, they achieved control over the number of C−H arylations by adding various types of phenol ligands.…”
Section: C−h Arylation Of Phosphinesmentioning
confidence: 99%
“…It is noteworthy that the integration of bromoferrocene into the phosphine scaffold has been achieved, culminating in the synthesis of a novel compound adorned with three ferrocene units. After we filed our work report, the You research group reported similar work on the phosphine-directed rhodium-catalyzed arylation reaction . Differing from our strategy, they achieved control over the number of C–H arylations by adding various types of phenol ligands.…”
Section: Introductionmentioning
confidence: 99%